2016
DOI: 10.4236/jep.2016.76083
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of End of Life Concrete Fines into Hardened Cement and Clean Sand

Abstract: One of the massive by-products of concrete to concrete recycling is the crushed concrete fines, that is often 0 -4mm. Although the construction sector is to some extent familiar with the utilization of the recycled coarse fraction (>4 mm), at present there is no high-quality application for fines due to its moisturized and contaminated nature. Here we present an effective recycling process on lab scale to separate the cementitious powder from the sandy part in the crushed concrete fines and deliver attractive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 16 publications
(22 reference statements)
0
6
0
2
Order By: Relevance
“…Use of untreated end‐of‐life binder in a cement kiln has produced a clinker with a mineralogical composition close to PC clinker and with ∼33% less process emissions from pyro‐processing (Gastaldi et al., 2015). However, technological improvements are generally required to enhance the quality of secondary NPCMs and kiln feed (i.e., to reduce contamination) produced from end‐of‐life CMs (Bakker et al., 2015; Lofti & Rem, 2016). Additionally, implementing these measures at the industrial scale requires changes to demolition practices, including increased collection rates, and improved separation of construction and demolition waste into distinct material types (Material Economics, 2019).…”
Section: Decarbonization Measuresmentioning
confidence: 99%
“…Use of untreated end‐of‐life binder in a cement kiln has produced a clinker with a mineralogical composition close to PC clinker and with ∼33% less process emissions from pyro‐processing (Gastaldi et al., 2015). However, technological improvements are generally required to enhance the quality of secondary NPCMs and kiln feed (i.e., to reduce contamination) produced from end‐of‐life CMs (Bakker et al., 2015; Lofti & Rem, 2016). Additionally, implementing these measures at the industrial scale requires changes to demolition practices, including increased collection rates, and improved separation of construction and demolition waste into distinct material types (Material Economics, 2019).…”
Section: Decarbonization Measuresmentioning
confidence: 99%
“…The gap between supply and demand for concrete will lead to the consumption of large amounts of resources, and the over-mining of raw materials for concrete also adds to the damage to the environment. EoL concrete accounts for the vast majority of C&DW (Lotfi and Rem, 2016), and the most viable solution for EoL concrete is recycling or upcycling. The conventional linear approach to recycling needs to be upgraded to a circular process, that is, secondary raw materials are obtained from EoL concrete for a green and sustainable solution (Cossu and Williams, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…can dramatically influence the possibilities of their correct reuse as recycled aggregate. Concerning RA, previous studies have demonstrated the possibility of evaluating building waste by HSI, assessing the presence of contaminants in RA, and classifying end-of-life construction materials [ 41 , 42 , 43 , 44 ]. However, few studies have been carried out on the monitoring of tiles coming from post-disaster building waste and on their possible reuse as RMA, despite their high presence in earthquake-damaged structures.…”
Section: Introductionmentioning
confidence: 99%